Healthcare antitrust, settlements, and the Federal Trade Commission - Langenfeld, James; Galeano, Edwin (Research in law and economics ;, 2018)
This volume of Research in Law and Economics contains articles that address important legal and economic developments in the areas of healthcare, intellectual property and labor settlements, competitive effects, cartel overcharges, and the U.S. Federal Trade Commission ("FTC"). Four of the articles were initially presented at a conference on healthcare competition in Washington, D.C., which was sponsored by the American Antitrust Institute, this journal, and Navigant Economics. These articles explore practices that are under challenge in pharmaceuticals, where the Federal Trade Commission has been extremely active, as well as issues involving hospital and health insurance mergers. They are followed by a long and detailed discussion of the current and historic role of economists and economic analysis at the Federal Trade Commission. The next two articles analyze different aspects of the French economy, pre-trial labor settlements and the impact of e-commerce on franchisees. The volume ends with three technical economics articles one on "upward pricing pressure", one on estimating price increases in cartel cases, and one critiquing a "meta-analysis" of research on the effectiveness of U.S. merger regulation. Taken together, these articles raise questions about appropriate competition policy, how to evaluate settlements and other firm behavior, and where economics and competition policy are headed.